Circular track finding using hough transform with discretized polling - Khasmidatul Akma Mohammad Kamal Azmi,; Wan Ahmad Tajuddin Wan Abdullah,; Au Diya Fatihah,; Mohammad Siddiq, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The objective of this paper was to show the results of single-parameter track finding based on the Hough transform method with discretized hits in an arbitrarily-sized Hough space. Each arbitrarily-sized Hough space was used to identify the most optimal hits with respect to a simulation-generated track. These hits will be useful in future studies involving multiple tracks as an identification of single-track potential size which will decrease the computational steps required to identify potential hits in multiple-track studies. These steps are well established in track finding research. However, the discretized method has not been applied fully because of uncertainty in identifying true hits in the Hough space. We have observed that by selecting the optimal discretized size, we can significantly improve the identification of true hits as it reduces the number of unrelated hits. We show that these steps are a more insightful technique compared to the traditional clustering technique by comparing our results to the K-Mean nearest neighbour method.